Dynamics of Public Communication of the Surabaya City Government in Tackling Online Prostitution - Sufa, Siska Armawati; Sumartias, Suwandi; Zubair, Feliza; Perbawasari, Susie; Rusmana, Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research explores the dynamics of public communication adopted by the Surabaya City Government in an effort to tackle the practice of online prostitution. The focus lies on a communication strategy that involves social media and star hotels as the main means. The case study approach in this research explores the city government's efforts to manage information, coordinate efforts with relevant stakeholders, and adapt messages to respond to complex challenges related to online prostitution. This research methodology includes interviews with city government representatives, social media content analysis, and related policy tracking. The research results illustrate the city government's efforts in creating effective and responsive communication strategies. Utilizing the power of social media to convey information, build public awareness, and gather cooperation from various star hotels to increase understanding and participation in dealing with online prostitution. However, challenges such as changes in behavioral patterns of online prostitution perpetrators and the evolution of social media are factors that influence the success of this public communication strategy. This study provides in-depth insight into the dynamics of public communication as the main strategy in dealing with sensitive issues such as online prostitution in the digital era. The implications of these findings can provide guidance for other city governments in designing similar communication strategies to solve similar problems.